Synthesis and characterization of solid 2-methoxycinnamylidenepyruvic acid - de Carvalho, Cláudio Teodoro; de Siqueira, Adriano Buzutti; Ionashiro, Elias Yuki; Pivatto, Marcos; Ionashiro, Massao (Eclética Química, 2008)
The 2-methoxycinnamylidenepyruvic acid (2-MeO-HCP) was synthesized and characterized for nuclear magnetic resonance (1H and 13C NMR), mass spectrometry (MS), Infrared spectroscopy (FTIR) and differential scanning calorimetry (DSC). The application of DSC for purity determination is well documented in literature and is used in the analysis of pure organic compounds. The molecular geometry and vibrational frequencies of 2-MeO-HCP have been calculated.